2005
DOI: 10.1523/jneurosci.3153-05.2005
|View full text |Cite
|
Sign up to set email alerts
|

Modifying the Subunit Composition of TASK Channels Alters the Modulation of a Leak Conductance in Cerebellar Granule Neurons

Abstract: Two-pore domain potassium (K 2P ) channel expression is believed to underlie the developmental emergence of a potassium leak conductance [I K(SO) ] in cerebellar granule neurons (CGNs), suggesting that K 2P function is an important determinant of the input conductance and resting membrane potential. To investigate the role that different K 2P channels may play in the regulation of CGN excitability, we generated a mouse lacking TASK-1, a K 2P channel known to have high expression levels in CGNs. In situ hybridi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
185
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(200 citation statements)
references
References 59 publications
(126 reference statements)
13
185
2
Order By: Relevance
“…units in mouse brain, these results are in good agreement with previous reports on different lines of TASK subunit knock-out mice (Aller et al, 2005;Linden et al, 2006;Brickley et al, 2007), although that group noted a slight decrement in performance of TASK-1 knock-outs on the rotarod (Aller et al, 2005) that our data do not reproduce.…”
Section: Task Channel Knock-out Micesupporting
confidence: 92%
See 1 more Smart Citation
“…units in mouse brain, these results are in good agreement with previous reports on different lines of TASK subunit knock-out mice (Aller et al, 2005;Linden et al, 2006;Brickley et al, 2007), although that group noted a slight decrement in performance of TASK-1 knock-outs on the rotarod (Aller et al, 2005) that our data do not reproduce.…”
Section: Task Channel Knock-out Micesupporting
confidence: 92%
“…knock-out mice (Aller et al, 2005;Brickley et al, 2007); in addition, that group reported no change in expression of a broad panel of K 2P channels in their TASK knock-out mouse lines (Aller et al, 2005;Brickley et al, 2007). Homozygous single TASK-1 Ϫ/Ϫ and TASK-3 Ϫ/Ϫ knock-out mice and doubly deleted TASK-1 Ϫ/Ϫ :TASK-3 Ϫ/Ϫ mice (hereafter called TASK Ϫ/Ϫ mice) were viable and presented with no obvious health problems.…”
Section: Task Channel Knock-out Micementioning
confidence: 99%
“…In the adult mouse forebrain the TASK-3 gene has much stronger expression than TASK-1. In particular, TASK-3 mRNA is abundant in layers 2 to 6 of the neocortex, CA1 hippocampal pyramidal cells, dentate granule cells, and the septum (38,39); the TASK-3 gene is also expressed in parvalbumin-positive GABAergic interneurons (40) in the hippocampus, some subtypes of which aid the generation of theta oscillations (41,42). The TASK-1 gene, by contrast, is poorly expressed in the mouse hippocampus (38).…”
Section: Discussionmentioning
confidence: 99%
“…Exon 2 excision in offspring was assessed by PCR using primers flanking this region (P3, 5Ј-TGCGAGCTTCAG-AGAGAGGATG-3Ј and P4, 5Ј-ATGCTCTAATCTCCAGTCTG-3Ј). TASK Ϫ/Ϫ mice were generated by crossing TASK3 Ϫ/Ϫ and TASK1 Ϫ/Ϫ mice (Aller et al, 2005). Resulting TASK3 ϩ/Ϫ TASK1 ϩ/Ϫ animals were further crossed, and double KO progeny (TASK Ϫ/Ϫ ) was identified by analyzing tail DNA.…”
Section: Methodsmentioning
confidence: 99%
“…This response was not significantly different from that of control or TASK1 Ϫ/Ϫ mice. However, because the absence of TASK3 in KO mice could be compensated by TASK1, we also tested glucosensing in TASK1 Ϫ/Ϫ mice (Aller et al, 2005). We also crossed TASK3 Ϫ/Ϫ and TASK1 Ϫ/Ϫ mice to obtain double TASK KO mice (hereafter termed TASK Ϫ/Ϫ mice).…”
Section: Glucose Inhibition In Orexin Neurons From Taskmentioning
confidence: 99%